Policy for transitioning childhood-onset growth hormone deficiency from pediatric to adult endocrine care in Belgium - Staels, Willem; De Schepper, Jean; Becker, Marianne; Lysy, Philippe; Klink, Daniel; Logghe, Karl; den Brinker, Marieken; Rochtus, Anne; Lapauw, Bruno; Cools, Martine; Alexopoulou, Orsalia; Bex, Marie; et al. (Frontiers in Endocrinology, 2024)
Growth hormone (GH) deficiency (GHD) in children and adolescents can vary in severity and origin, with GH replacement therapy proving effective in achieving genetic target height.Optimal outcomes are seen in those treated early and with higher doses. As patients approach adult height, priorities shift towards optimizing metabolic effects, maintaining body composition, and enhancing bone mass and muscle strength. Transitioning from pediatric to adult care presents challenges, including accurately identifying candidates for continued GH therapy, reevaluating persistent GHD, and preventing treatment discontinuation. Assessing readiness for transition and self-management skills is crucial. This Policy and Practice Review provides a comprehensive overview of current policies, regulations, and guidelines pertinent to managing GHD transition in Belgium. We integrate perspectives from national academic and nonacademic clinical stakeholders in pediatric and adult endocrine care to provide an updated policy framework. This framework underscores the importance of sustained GH therapy during transition, particularly for individuals with persistent GHD, with the goal of optimizing practices and improving outcomes during this critical period.